Struggling with Citational Politics as a Pathway to Unlearning and Relearning for Collective Action - Crespo, Christina; Liboiron, Max; Flynn, Alex; Rivers, Molly; Cotter, Riley; Liu, Rui; Lombeida, Dome; Hawkins, Kaitlyn; Duman, Nadia; Arif, Abu; Allen, Edward; Healey, Natasha; et al. (KULA, 2026)
There is a growing movement committed to the values of equitable and just citation, but the material practices of altering citational politics are more challenging. For instance, researchers in the Global South are under-cited, but how many citations are enough to correct this bias? How do we best determine when an author is from the Global South to begin with? We present a case study where social and natural science researchers (the authors) spent years engaged in the material practices of citational politics at the Civic Laboratory for Environmental Action Research (CLEAR). Our findings show that there were notable changes at the individual and collective levels as participants tried to change the status quo, and we use Gloria Anzaldúa’s pathway to conocimiento as an organizing framework for explaining the process of unlearning and learning that occurs through engaging with citational politics. The pathway moves through seven non-linear stages on the way to conocimiento: (1) arrebato/the rupture, when the reality of citational politics is fully understood; (2) liminal space, characterized by more questions than answers; (3) a retreat to pre-rupture/arrebato politics in the face of difficult ideas (backsliding); (4) the crossing, a step in ethical learning that moves the learner from thinking to action; (5) creating new stories where new individual and collective norms emerge; (6) the clash, a stage where these new norms clash against the status quo again; (7) and finally chores, the mundane, regular practices that maintain an amended status quo. Our analysis of the process is designed to both support citational politics practices in particular and provide a framework with examples of how to facilitate and anticipate changes in engaged, collective social change work in general.